Pengaruh Terapi Pijat Oksitosin Terhadap Pengeluaran Asi Pada Ibu Post Partum Di Ruang Post Maternal Partum (PMP) Puskesmas Bumiayu Kabupaten Brebes 2021 - Ahmad Zakiudin; Fitriyani Setiyaningsih (Jurnal Sains dan Kesehatan, 2021)
The puerperal period is also called the post partum or puerperium period, which is the time between the birth of the baby and the placenta leaving the uterus until the return of the reproductive organs to a normal state as before childbirth. The puerperium lasts six weeks. The purpose of this study was to determine the effect of oxytocin massage on breastfeeding in post partum mothers in the post maternal partum (PMP) room at Bumiayu Health Center, Brebes Regency 2021. The research method used is pre-experiment (experimental activity that aims to determine an effect that arises as a result of certain treatments) using one-group pretest-post test design, namely an experimental design that uses one group of subjects and takes measurements before and after treatment. on the subject. This design is to determine the effects before and after treatment. The analysis in this study used the t-test. From the results of statistical testing using the T-test, the significance value was 0.000 (p <0.05). So it can be concluded statistically Ha is accepted and Ho is rejected, meaning that it can be concluded that there is an effect of oxytocin massage therapy on breastfeeding in post partum mothers at Bumiayu Health Center. In connection with the results of this study, it is hoped that post partum mothers with the help of their husbands or families at home can inform the surrounding community so that they can increase their knowledge and insight to apply oxytocin massage as a solution to overcome the problem of unsanitary breastfeeding.